UslÅ«b Al-QirÄah Al-Saá¹hiyah wa Tarqiyah MahÄrah QirÄah Al-Naá¹£ - Ahmad Habibi Syahid (Arabic Education Program IAIN Pekalongan, 2020)
The right method will produce the desired result. Such a method includes the one that helps improve the ability to read the text. The ability to read and comprehend a text is one of the goals in learning reading skills. Several learning methods and techniques have a significant impact on the improved reading skills, one of which is speed reading technique such as skimming. Skimming aims to quickly understand the text by finding the main idea of the passage as a whole. This study aims to determine the significance of the skimming technique to help understand a text. This research is also intended to determine the level of students' ability in understanding the text by using the skimming reading technique. A descriptive analysis research, this study also explains the causes and effects of the variables x and y. The findings of this study indicate the significance of the skimming reading technique in improving students' reading skills.